2020
DOI: 10.1264/jsme2.me20114
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of γ-Aminobutyric Acid Chemotaxis for Virulence of <i>Pseudomonas syringae</i> pv. <i>tabaci</i> 6605

Abstract: γ-Aminobutyric acid (GABA) is a widely distributed non-proteinogenic amino acid that accumulates in plants under biotic and abiotic stress conditions. Recent studies suggested that GABA also functions as an intracellular signaling molecule in plants and in signals mediating interactions between plants and phytopathogenic bacteria. However, the molecular mechanisms underlying GABA responses to bacterial pathogens remain unknown. In the present study, a GABA receptor, named McpG, was conserved in the highly moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The Pta 6605 chemotaxis system plays a significant role in virulence ( Tumewu et al , 2021b ). Furthermore, mutations in the mcp genes for γ-aminobutyric acid and amino acids had a prominent impact on Pta 6605 fitness in host plants ( Tumewu et al , 2020 ; 2021a ). To elucidate the role of aerotaxis on virulence by Pta 6605, a flood inoculation assay was performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Pta 6605 chemotaxis system plays a significant role in virulence ( Tumewu et al , 2021b ). Furthermore, mutations in the mcp genes for γ-aminobutyric acid and amino acids had a prominent impact on Pta 6605 fitness in host plants ( Tumewu et al , 2020 ; 2021a ). To elucidate the role of aerotaxis on virulence by Pta 6605, a flood inoculation assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the surface motility of aer mutant strains, motility assays were performed on semisolid agar medium as previously described ( Tumewu et al , 2020 ). Bacterial strains were cultured overnight in LB broth supplemented with 10‍ ‍mM MgCl 2 and resuspended in 10‍ ‍mM of MgSO 4 at an OD 600 of 0.1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found the requirements of cheA2 and cheY2 of Pta 6605 in chemotaxis and virulence on host tobacco plant (unpublished results). Recently, it was reported that the defective mutant of chemoreceptor of amino acid, PscA in Pto DC3000 and chemoreceptor of γ-aminobutyric acid, McpG in Pta 6605 reduced virulence [ 16 , 17 ]. Furthermore, PscA and McpG are not only chemoreceptors but also regulator of virulence related traits.…”
mentioning
confidence: 99%